Enhancing Principal Effectiveness: A Meta-Analysis on the Roles of Academic Supervision and Instructional Leadership - Tati Maryati; Merry Lapasau; Sunar Abdul Wahid (Postgraduate, University of Mataram, 2025)
School principal performance plays a crucial role in achieving institutional goals through effective leadership and academic supervision. While previous studies have demonstrated that both academic supervision and instructional leadership significantly influence principal performance, there remains a need for a comprehensive synthesis of empirical findings to clarify the strength and consistency of this relationship. This meta-analysis study focuses on supervision conducted by educational supervisors and instructional leadership as the primary factors affecting principal performance. A total of 27 empirical studies published between 2018 and 2025 were carefully selected based on predetermined inclusion criteria from the Google Scholar, SINTA, and Scopus databases. Meta-analytic procedures were implemented using JASP version 0.14.10, employing random-effects models to calculate effect sizes and test for heterogeneity and publication bias. The analysis revealed significant positive correlations between academic supervision (r = 0.611, p < 0.01) and instructional leadership (r = 0.578, p < 0.01) with principal performance. Results indicated moderate heterogeneity among studies, suggesting variability due to contextual factors, while no evidence of publication bias was detected. These findings affirm the critical influence of academic supervision and instructional leadership on principal effectiveness. The study highlights the importance of leadership development and the formulation of institutional policies that integrate supervisory and instructional dimensions to strengthen educational outcomes.